2020
DOI: 10.1101/2020.08.14.250258
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of Severe Acute Respiratory Syndrome Coronavirus 2 main protease by tafenoquinein vitro

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causing the current pandemic, coronavirus disease 2019 (COVID-19), has taken a huge toll on human lives and the global economy. Therefore, effective treatments against this disease are urgently needed. Here, we established a fluorescence resonance energy transfer (FRET)-based high-throughput screening platform to screen compound libraries to identify drugs targeting the SARS-CoV-2 main protease (Mpro), in particular those which are FDA-approved, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The maximal plasmatic concentration of tafenoquine, used for Plasmodium vivax infections, exhibited interindividual variability, its bioavailability being greatly influenced by high-fat meals. Preliminary studies demonstrated that tafenoquine had an anti-SARS-CoV-2 activity in Vero E6 cells in two studies that found an EC 50 from 2.5 to 16 μM [ 133 , 134 ].…”
Section: Resultsmentioning
confidence: 99%
“…The maximal plasmatic concentration of tafenoquine, used for Plasmodium vivax infections, exhibited interindividual variability, its bioavailability being greatly influenced by high-fat meals. Preliminary studies demonstrated that tafenoquine had an anti-SARS-CoV-2 activity in Vero E6 cells in two studies that found an EC 50 from 2.5 to 16 μM [ 133 , 134 ].…”
Section: Resultsmentioning
confidence: 99%
“…4 ( 10 ) Clofazimine In vivo 0.31 Preclinical 68 Replication inhibitors Target 3CLpro Fig. 5 ( 11 ) Tafenoquine In vitro 2.5 Preclinical 72 In vitro ∼ 2.6 ≥ 50 Preclinical 73 Fig. 5 ( 12 ) 12 In vitro 0.25 ± 0.15 >100 Preclinical 74 Fig.…”
Section: Sars-cov-2 Life Cycle and Potential Targets For The Development Of Small-molecule Inhibitors Against Sars-cov-2 Infectionmentioning
confidence: 99%
“…Chen and his colleagues 72 established a HTS platform based on fluorescence resonance energy transfer (FRET) to identify drugs targeting the SARS-CoV-2 3CLpro from compound libraries, especially FDA-approved drugs, to be used immediately to treat patients with COVID-19. Their findings indicate that the 8-aminoquinoline antimalarial drug tafenoquine [ Fig.…”
Section: Small-molecule Sars-cov-2 Inhibitors Targeting Viral Proteinsmentioning
confidence: 99%
“…Resultantly, 80 (tafenoquine), an antimalarial drug, was found to be endowed with the potential to exert conformational change in SARS-CoV-2 Mpro, thereby diminishing the protease activity. Also, the drug significantly inhibited SARS-CoV-2 infection in the cell culture system (IC 50 = 2.5 µmol/L) [ 102 ]. In another study, 80 (Tafenoquine) was found to be more potent than hydroxychloroquine in inhibiting SARS-CoV-2 in VERO E6 cells (Fig.…”
Section: Protease Inhibitorsmentioning
confidence: 99%